Health status and health behaviours of the Hungarian homeless caregivers. (30th September 2020) - Nagy-Borsy, E; Szeitl, B; Kiss, I; Rákosy, Z s
Abstract: Background: So far little attention has been given to the physical and mental health of homeless caregivers. Their health behavior can serve as role model for homeless people. For this reason, the aim of our study was to identify the health problems and health behavior of homeless caregivers. Methods: We conducted a representative nationwide survey including 559 individuals to determine the homeless caregivers' health status and health behavior. The results were compared with the age and sex adjusted data of the European Health Interview Survey 2014 that was carried out in the general Hungarian adult population. Results: The majority of participants (71%) gave positive ratings to their own health, they considered their health status significantly better compared to the general population (p = 0.002). Of them 34% had chronic disease compared to the 39% of the general population, 27% experienced limitation because of their health problems. Their mental status was worse than the general population, 40% had depression compared to the 23% of the reference. Majority of them (59%) were obese or overweight, those who lived in countryside were more likely to be obese or overweight than those who lived in the capital (p = 0.02). Only 41% of them consumed fruits and 26% of them consumed vegetables on a daily basis. These rates were significantly lower compared to the general population, p < 0.008. Most of them (62%) were occasional drinker. The prevalence of current smokers (37%) were higher among them than in the general population (32%) Conclusions: In conclusion, the homeless caregivers had worse mental health status than the general Hungarian population. They were also characterized by unhealthy lifestyle such as inadequate fruit and vegetable consumption and high rate of smoking. As caregivers serve as a role model for homeless people, supporting their health and health behavior might have strong effect on health of homeless people as well. Key message: The survey's findings indicate the health program for homeless caregivers would be worthwhile specially focusing on smoking cessation, healthy eating and mental health.